Implementation of the Green Economy in the Context of the 2025 Clean Waste Bantul Movement (Bantul Bersama) - Mahrus Lutfi Adi Kurniawan; Suripto (Asian Journal of Community Services, 2022)
Green Economy or green economy is an economic idea that aims to improve the welfare and social equality of the community, while reducing the risk of environmental damage significantly. So far, the economic aspect is more dominant than the environmental aspect so that environmental sustainability is not maintained and produces negative effects/externalities that can harm residents in the surrounding environment. Environmental damage is a full concern for economists, giving rise to the concept of a green economy or better known as a green economy.